People, Texts and Artefacts Cultural Transmission in the Medieval Norman Worlds - Bates, David; D'Angelo, Edoardo; van Houts, Elisabeth (IHR Conference Series, 2018)
This volume is based on two international conferences held in 2013 and 2014 at Ariano Irpino, and at Emmanuel College, Cambridge. It contains essays by leading scholars in the field. Like the conferences, the volume seeks to enhance interdisciplinary and international dialogue between those who work on the Normans and their conquests in northern and southern Europe in an original way. This collection has as its central theme issues related to cultural transfer, treated as being of a pan-European kind across the societies that the Normans conquered and as occurring within the distinct societies of the northern and southern conquests. These issues are also shown to be an aspect of the interaction between the Normans and the peoples they subjugated, among whom many then settled.